FINANCING DIGITAL TRANSFORMATION IN EMERGING MARKET SPECIAL ECONOMIC ZONES (European Journal of Economics, Finance and Business Development, 2026)
This paper examines the critical issues surrounding the financing of digital transformation initiatives within Special Economic Zones (SEZs) in emerging markets. It identifies key challenges such as inadequate infrastructure, limited access to capital, regulatory uncertainties, and a lack of skilled human resources that hinder the successful implementation of digital projects. The study explores various financing mechanisms, including public-private partnerships, venture capital, green finance, and international development aid, and analyzes their suitability for SEZs. Furthermore, it discusses the potential of emerging financial technologies (fintech) to bridge financing gaps and accelerate digital adoption. The paper concludes by offering policy recommendations aimed at creating a more conducive financial ecosystem for digital transformation in these strategic economic enclaves.